Editorial Note - Mushtaqur Rahman (International Institute of Islamic Thought, 1987)
The complex and bewildering variety of issues and problems facing the present-day Muslims have made them singularly hard pressed to develop rational strategies and efficient policies. The intensity and multiplicity of demands have increased to such an extent that in recent years efforts to Islamize knowledge or recreate a Muslim way of life needs congruent thinking and prudent planning. In thinking about this question, at least two issues of adaptability and sustainability take the front stage. Adaptability would mean that Islamic social sciences and cultural habits should be sought out and adopted. This way would not be an imposition of alien models or values, but a reversion to the Qur'an and Sunnah for knowledge and guidance. Once adopted, either from traditional or modem Islamized social science, it ought to be maintained against all odds. The American Journal of Islamic Social Sciences has been trying for the last four years to initiate such changes in the social and individual behavior, and Islamize the knowledge with the assistance of the International Institute of Islamic Thought and the Association of Muslim Social Scientists. My predecesssor, Sulayman Nyang, left such a strong record of service that would be difficult for anyone to meet. I was conscious of this challenge when I was asked and accepted to succeed him. I knew of course that I could always count on his support to maintain the Journal at the same standard, if not higher. This issue has three sections. Section one includes two papers on matters concerning the Islamic Thought. The first paper by Ahmad Zaki Hammad presents Ghazali's approach to usul-al-Jiqh, divided into three elements: (i) ahkam, (ii) adilla (source), and (iii) mujtahid.. . .Of these three, the paper provides broader explanation only of ahkams, leaving the other two for subsequent presentations. The second paper by Bogdan Meckowski compares Ibn Khaldun with Adam Smith, and other modern economists, giving Ibn Khaldun the prominent place he deserves. With remarkable skill, Mieckowski establishes that Ibn Khaldun favored laissez-faire, and opposed a socialized or monopolistic production. Accordq to Mieckowski, most modern economists borrow heavily from Ibn Khaldun without acknowledging or crediting him in their works ...